Saturday

April 19, 2014

April 19, 2014

Posted by **josh** on Thursday, March 1, 2012 at 4:24pm.

(4 − 2x)−2

(y − z)−3

(x − 5y)0

- math -
**Steve**, Thursday, March 1, 2012 at 4:39pm(4-2(-2))-2 = (4-(-4)) = 4+4) = 8

(4-(-3))-3 = (4+3)-3 = 4+3-3 = 4

(-2-5(4))0 = 0

(anything times 0 = 0)

**Related Questions**

Advanced Math I - If a * b = a - 3b and a # b = 2a + 3b, evaluate the expression...

math 115 - 1. divide 36/-4= 9 is this correct? 2. evaluate the expression |-5 +3...

math - Evaluate the exponential equation for three positive values of x, three ...

Math PIZZAZZZ - how does a rodeo star get around?? well if you cant give me an ...

math 115 - 1.evalute the expression -8 + 15 = 7 is this answer correct? 2....

Algebra - Totally lost here! Evaluate the exponential equation for three ...

Algebra - Evaluate the exponential equation for three positive values of x, ...

Intermediate Algebra - Evaluate the exponential equation for three positive ...

Intermediate algebra - Evaluate the exponential equation for three positive ...

algebra, logarithms - Evaluate the exponential equation for three positive ...